Case Report: Extragonadal Yolk Sac Tumors Originating From the Endometrium and the Broad Ligament: A Case Series and Literature Review - Cheng, Xianzhong; Zhao, Qian; Xu, Xia; Guo, Wenwen; Gu, Hongyuan; Zhou, Rui; Chen, Chen; Ma, Dawei; Wu, Yinan; Ni, Jing; Chen, Xiaoxiang (Frontiers in Oncology, 2021)
Yolk sac tumors (YSTs) of the endometrium and the broad ligament are very rare, with only 29 cases and 1 case of each other reported before in the English literature. Due to lack of standard guidelines, the treatment strategies of these diseases are controversial. Here, we share two cases of YSTs originating from the endometrium and the broad ligament respectively and review related literature. A 35-year-old woman was diagnosed with endometrial YST in our center and underwent surgery followed by chemotherapy with BEP (bleomycin, cisplatin and etoposide) regimen for 6 courses. After follow-up for 21 months, there is still no evidence of relapse. Another 36-year-old woman was admitted to our department with YST of the broad ligament. She was treated with surgery followed by chemotherapy with BEP regimen and was lost to follow-up after completing therapy. The case of endometrial YST we shared was similar to cases reported before, while the case with YST of the broad ligament we shared was the second case reported worldwide. Both of these two cases were treated with surgery combined with surgery.